Decade after hathi committee / edited by B. Ekbal - B. Ekbal (ed.) (Kerala, 1988)
The Hathi Committee appointed by the Government of India to study and suggest measures to improve the drug industry in India, submitted its report more than a decade ago.. This report is still considered, both within and outside India, as the most authentic and exhaustive study of the Indian Pharmaceutical Industry
Keywords: Pharmaceuticals